Comportamiento organizacional y su incidencia en la práctica y actitudes de la secretaria del Departamento de Catastro del Gobierno Autónomo Descentralizado de la ciudad de Babahoyo, Provincia de Los Ríos - Arzube Banchón, Yvette Andreina (2020)
The present work is the result of an investigation that aims to investigate the organizational behavior and its impact on the practices and attitudes of the secretaries in the cadastre department of the Decentralized Autonomous Government of Babahoyo Los Ríos Province, it is justified to establish whether the Organizational behavior influences the practices and attitudes in the activities carried out by the secretaries at the time of serving the user, demonstrating kindness, patience, tolerance, efficiency and discretion; For this purpose, the diagnosis was carried out through surveys directed at secretaries and users. This study was carried out through descriptive research which allowed to know the characteristics of the variable to be investigated using a survey consisting of five questions and an interview of options consisting of five items by instrument, evidencing by the secretary an adequate organizational behavior affects both the work environment and the attention of the user, while the clients who receive the attention from the secretary stated the opposite. Taking into account that organizational behavior is the main engine of a company, becoming so important to the point that it is responsible for the tranquility and efficiency of the organization, allowing staff to have adequate attitudes to work.